2015
DOI: 10.17795/bhs-31211
|View full text |Cite
|
Sign up to set email alerts
|

Screen Time and Physical Activity in Overweight and Obese Students

Abstract: Background: One of the most important threats for children's health status is being overweight and obesity, and related causes such as screen time prevalence. Prevalence of being overweight and obesity in children is associated with health risk consequences in adulthood. Objectives: The purpose of this study was to assess the prevalence of screen time and physical activity in overweight and obese students. Patients and Methods: In this cross sectional descriptive study we randomly selected 302 students, from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Men and boys have been shown to spend more time in front of a screen than women and girls (Hosseinzadeh & Ahmadabad, 2015;Husárová et al, 2015), which is partially in agreement with the results of the present study in which heterosexual women were found to be better protected against this health-related risk behavior. Hosseinzadeh and Ahmadabad (2015) reported that, from an early age, parents in Iran tend to reduce girls' access to games compared to the access permitted to boys, which may go towards justifying, at least in part, the lesser exposure of girls to long periods of screen time. There are no studies on this health behavior as a function of sexual orientation, further reinforcing the importance of the present study and justifying the recommendation for future studies on this subject.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Men and boys have been shown to spend more time in front of a screen than women and girls (Hosseinzadeh & Ahmadabad, 2015;Husárová et al, 2015), which is partially in agreement with the results of the present study in which heterosexual women were found to be better protected against this health-related risk behavior. Hosseinzadeh and Ahmadabad (2015) reported that, from an early age, parents in Iran tend to reduce girls' access to games compared to the access permitted to boys, which may go towards justifying, at least in part, the lesser exposure of girls to long periods of screen time. There are no studies on this health behavior as a function of sexual orientation, further reinforcing the importance of the present study and justifying the recommendation for future studies on this subject.…”
Section: Discussionsupporting
confidence: 92%
“…Although relatively better protected with respect to the other behaviors analyzed, this group was at a greater risk insofar as the practice of leisure-time physical activity is concerned. A major difference between the sexes has been reported, with women practicing less physical activity than men (Azevedo et al, 2007;Hosseinzadeh & Ahmadabad, 2015;Saffer et al, 2013;Salles-Costa et al, 2003). As in the case of smoking and alcohol consumption, one explanation for these differences may be the association between the practice of physical activity and male norms (De Visser & McDonnell, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some mediators that affect physical activity such as knowledge and attitude. Some barriers such as lack of time and bad environments may impede doing physical activities (6,7). Nursing and midwifery students, candidates for bachelor of science, should pass 138 credit units in four years.…”
Section: Introductionmentioning
confidence: 99%